2012
DOI: 10.1002/cncr.27407
|View full text |Cite
|
Sign up to set email alerts
|

Single versus multiple primary melanomas

Abstract: BACKGROUND:In patients with multiple primary melanomas (MPM), mean tumor thickness tends to decrease from the first melanoma to the second melanoma, and prognosis may be improved compared with the prognosis for patients who have a single primary melanoma (SPM). In this study, the authors compared the clinicopathologic features of patients with MPM and SPM to better characterize the differences between these 2 groups and to determine whether or not there is an inherent difference in tumor aggression. METHODS: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
84
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(105 citation statements)
references
References 45 publications
16
84
4
1
Order By: Relevance
“…In 35% of patients the second melanoma was diagnosed within 1 year of the diagnosis of the first melanoma (see Table 3), which is similar to previous reports. 5,6 This lower Clark level for subsequent melanomas and the increased detection of a subsequent melanoma in the first year is likely to be due to both increased physician's examination and patients' selfexamination. The lower Clark level of subsequent melanomas may also reflect improved sun-protection and sunscreen usage by these patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In 35% of patients the second melanoma was diagnosed within 1 year of the diagnosis of the first melanoma (see Table 3), which is similar to previous reports. 5,6 This lower Clark level for subsequent melanomas and the increased detection of a subsequent melanoma in the first year is likely to be due to both increased physician's examination and patients' selfexamination. The lower Clark level of subsequent melanomas may also reflect improved sun-protection and sunscreen usage by these patients.…”
Section: Discussionmentioning
confidence: 96%
“…1 Significant risk factors for the development of melanoma include the number of common naevi, a positive family history of melanoma, age over 60 years, dysplastic naevus syndrome and atypical naevi. [3][4][5][6][7] Other factors such as fair skin or eye colour, increased freckling and number of sunburns are also important risk factors for the development of skin cancer. 8,9 The regular use of sunscreen can reduce the rate of squamous cell carcinoma (SCC) and melanoma development.…”
Section: Introductionmentioning
confidence: 99%
“…8 Another study investigated whether a less aggressive biology in MPM, represented by mitotic rate, was a possible explanation for the generally thinner lesions in MPM and SPM but concluded that it was not and that other factors such as increased surveillance or genetic constitution probably contribute. 10 …”
Section: Discussionmentioning
confidence: 99%
“…That similar mitotic rates have been observed for SPM and MPM suggests little difference in underlying biologic aggressiveness between SPM and MPM lesions. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation